DETERMINAN TINGKAT PENGANGGURAN DAN KEMISKINAN DI WILAYAH SARBAGITA PROVINSI BALI - Puspita, Ni Putu Priska Hendra; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The SARBAGITA region which functions as a National Activity Center is a strategy for developing service systems for urban centers and centers of economic growth. It is hoped that growth will become more competitive and more effective in developing regions to minimize poverty. This study aims to analyze the effect of economic growth, MSEs, HDI and PMA directly on TPT and poverty in the SARBAGITA region of Bali Province. To determine the role of TPT in mediating the effect of economic growth, MSEs, HDI and PMA on poverty in the SARBAGITA region of Bali Province. The analysis technique used in this study is path analysis. The results showed that economic growth had no effect on TPT. UMK and PMA have a significant positive effect on TPT while HDI has a significant positive effect on TPT in the SARBAGITA region of Bali Province. Economic growth, HDI and PMA have a significant negative effect on poverty. UMK and TPT did not have a significant effect on poverty in the SARBAGITA region of the Province of Bali. TPT does not mediate the influence of economic growth, MSEs, HDI and PMA on poverty in the SARBAGITA region of Bali Province.